Can a Hands-On Physics Project Lab be Delivered Effectively as a Distance Lab? - Moosvi, Firas; Reinsberg, Stefan; Rieger, Georg (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2019)
In this article, we examine whether an inquiry-based, hands-on physics lab can be delivered effectively as a distance lab. In science and engineering, hands-on distance labs are rare and open-ended project labs in physics have not been reported in the literature. Our introductory physics lab at a large Canadian research university features hands-on experiments that can be performed at home with common materials and online support, as well as a capstone project that serves as the main assessment of the lab. After transitioning the lab from face-to-face instruction to a distance format, we compared the capstone project scores of the two lab formats by conducting an analysis of variance, which showed no significant differences in the overall scores. However, our study revealed two areas that need improvements in instruction, namely data analysis and formulating a clear goal or research question. Focus group interviews showed that students in the distance lab did not perceive the capstone project as authentic science and that they would have preferred a campus lab format. Overall our results suggest that the distance project lab discussed here might be an acceptable substitute for a campus lab and might also be suitable for other distance courses in science.